RANCANG BANGUN BATTERY PACK LITHIUM 144V/220AH UNTUK MOBIL LISTRIK - Sunardi, Egi; Maria Bestarina Laili; Jelita Permatasari; Hanopa Abdul Hidayah; Diky Zakaria (Department of Electrical Engineering, UNJANI, 2025)
The development of electric vehicle (EV) technology is advancing rapidly in various aspects, driven by the need for environmentally friendly and efficient transportation solutions. Electric vehicles are powered by electric motors, which require an energy source in the form of a battery arranged into a battery pack. A battery pack consists of battery cells arranged in series and parallel to meet the energy specifications required by the electric vehicle. Currently, lithium batteries are considered the best choice for electric vehicles due to their advantages in energy density and cost per cycle compared to other types of batteries. In the design of this battery pack, the vehicle's specifications require a voltage of 144V to power the electric motor, with a target usage time of 5 hours, leading to a designed capacity of 220Ah. The battery used is a Lithium Ferro Phosphate (LFP) type with specifications of 3.2V and 22Ah. Based on mathematical calculations, the battery pack design utilizes 10 batteries in parallel and 48 in series to achieve the required specifications. The design also takes into account the maximum storage space inside the vehicle, with the battery pack divided into two banks placed in the front and rear of the vehicle to maintain a balanced center of gravity. After assembly, voltage measurements showed that the maximum voltage achieved was 153.6V. Testing was conducted after the batteries were installed in the vehicle, which showed that the vehicle could be operated for 19 hours with an average current of 11.5A. From the test results, the battery capacity was calculated to be approximately 218.5Ah. The test results indicate that the battery performance does not fully match the theoretical calculations, due to factors such as battery characteristics and energy losses in the vehicle system.